2013
DOI: 10.1038/emboj.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

Srs2 mediates PCNA-SUMO-dependent inhibition of DNA repair synthesis

Abstract: Completion of DNA replication needs to be ensured even when challenged with fork progression problems or DNA damage. PCNA and its modifications constitute a molecular switch to control distinct repair pathways. In yeast, SUMOylated PCNA (S-PCNA) recruits Srs2 to sites of replication where Srs2 can disrupt Rad51 filaments and prevent homologous recombination (HR). We report here an unexpected additional mechanism by which S-PCNA and Srs2 block the synthesis-dependent extension of a recombination intermediate, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 85 publications
(158 reference statements)
6
74
0
1
Order By: Relevance
“…At the C‐terminus, Srs2 contains a variety of regulatory motifs, which are modulated through post‐translational modifications and/or required for the interactions of Srs2 with other proteins, including PCNA, and these are important for its role at replication forks (Papouli et al , 2005; Pfander et al , 2005; Burgess et al , 2009) and regulation of the D‐loop extension (Burkovics et al , 2013). However, most of the C‐terminus was not required for the role of Srs2 in DSB repair via de novo telomere addition, BIR and SSA (Fig 8A–D).…”
Section: Resultsmentioning
confidence: 99%
“…At the C‐terminus, Srs2 contains a variety of regulatory motifs, which are modulated through post‐translational modifications and/or required for the interactions of Srs2 with other proteins, including PCNA, and these are important for its role at replication forks (Papouli et al , 2005; Pfander et al , 2005; Burgess et al , 2009) and regulation of the D‐loop extension (Burkovics et al , 2013). However, most of the C‐terminus was not required for the role of Srs2 in DSB repair via de novo telomere addition, BIR and SSA (Fig 8A–D).…”
Section: Resultsmentioning
confidence: 99%
“…Srs2 is a translocase that prevents HR by dismantling Rad51 filaments (Krejci et al 2003;Veaute et al 2003) and regulates the extent of DNA repair synthesis in a SUMO-PCNA-dependent manner (Burkovics et al 2013). Here we uncovered that, in response to damage during replication, SUMOmediated interactions and proteasome-dependent turnover intersect to promote local down-regulation of Srs2 and facilitate recombination-mediated DDT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that Mus81-Mms4 and Srs2 promote crossover and non-crossover pathways, respectively, the functional crosstalk between Mus81-Mms4 and Srs2 may be regulated to balance the repair pathway choice. In a separate study, binding of Srs2 to SUMO-PCNA has been found to attenuate repair synthesis by occluding Polδ and Polη from binding to PCNA (Burkovics et al 2013). Again, this activity does not require the helicase activity of Srs2 (Burkovics et al 2013).…”
Section: Non-motor Roles For Srs2mentioning
confidence: 99%